Defect-free nanofiltration membrane containing TaPa-COF interlayer

Through in-situ alternation, TpPa-COF interlayer nanofiltration membrane was prepared, combined with interfacial polymerization and in-situ growth, the existing COFs nanosheet preparation process and insufficient adhesion were solved, and efficient mono/divalent ion separation was achieved and the flux and durability of the membrane was improved.

CN119793215AActive Publication Date: 2025-04-11NANJING TECH UNIV +1

Patent Information

Application Number
CN202411651648.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-11
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The preparation process of existing COFs nanosheets in mono/divalent ion separation is cumbersome and time-consuming, the flux is reduced, and the R&D cost is high, so it cannot achieve industrial application. At the same time, the insufficient adhesion between the COF layer and the substrate leads to a decrease in the mechanical strength and durability of the film.

Method used

In situ interlaced nanofiltration membrane was prepared by in situ interlacing, and TpPa-COF film interlaced layer was prepared by interfacial polymerization and in situ growth method, and a polyamide layer was formed on the surface to improve the hydrophilicity of the membrane and the removal ability of divalent cations.

Benefits of technology

It achieves the high separation effect while maintaining ideal water flux, solves the difficulties such as defects in traditional NF membrane separation layers, easy pollution and low recycling, and improves the mechanical strength and durability of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a preparation method of a nanofiltration membrane containing a covalent organic framework (COF) interlayer. The nanofiltration membrane (NF) comprises a base membrane, an interlayer and a separation surface layer. The interlayer is formed by in-situ growth of polyphenol and diamine under the action of an oxidizing agent, and the separation surface layer is formed by an aqueous-phase active monomer and multi-element acyl chloride through an interfacial polymerization reaction. According to the invention, an imino covalent organic framework (TpPa-COF) film interlayer is introduced, and a surface polyamide layer is prepared through interfacial polymerization, so that the hydrophilicity of the film and the ability of removing divalent cations are improved. The invention aims to solve the problem of balance between low flux and high separation effect of an NF membrane in separation of monovalent / divalent cations, maintain ideal water flux while ensuring high separation effect, and solve the problem that a traditional NF membrane separation layer has defects. The two-dimensional TpPa-COF material can effectively control the pore size distribution and hydrophilicity of the surface of the substrate and improve the separation performance of the composite membrane. The preparation method is simple, and the obtained nanofiltration membrane has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for in-situ intergrowth preparation of a COFs sandwich nanofiltration membrane, belonging to the technical field of membrane preparation. The nanofiltration membrane has the advantages of high pure water flux, high selectivity, good anti-fouling effect, etc., and is suitable for fields such as ion separation. Background Art

[0002] High-salinity wastewater treatment is a global problem. my country produces more than 300 million cubic meters of high-salinity wastewater each year, resulting in more than 10 million tons of high-salinity hazardous waste, most of which have not been properly treated, causing huge pressure on the ecological environment. Although high-salinity wastewater regeneration treatment can remove most of the harmful substances, a small amount of impurities such as Mg still remain. 2+ 、Na + Monovalent and divalent cations, etc. These impurities need to be treated in the brine refining of the chlor-alkali industry to ensure the normal operation of the electrolysis process and obtain refined brine that meets the requirements. By separating monovalent and divalent ions, the required resources can be extracted from high-salt wastewater.

[0003] In the past few decades, heavy metal ions have been removed by traditional methods such as chemical precipitation, ion flotation, ion exchange, coagulation / flocculation, adsorption and electrochemical removal. However, these low-cost methods have problems such as incomplete heavy metal removal, high energy consumption and the production of toxic sludge.

[0004] Existing solutions: COFs are currently used for the separation of monovalent and divalent ions. For example, CN202410632726.0 discloses a method for preparing a COF@Dopamine composite membrane and its ion separation application, but the process of preparing COFs nanosheets is cumbersome and time-consuming, and the flux decreases significantly, the research and development cost is high, and it cannot be applied industrially. The two-dimensional TpPa-COF material is an imine-based covalent organic framework with the advantages of large specific surface area, high porosity, easy functionalization and strong design. Introducing it into the membrane can effectively control the pore size distribution and hydrophilicity of the membrane surface, and improve the separation performance of the composite membrane. However, the introduction of COFs into the membrane to separate monovalent and divalent cations also has the problem of insufficient adhesion between the COF layer and the substrate, resulting in a decrease in the mechanical strength and durability of the membrane. The in-situ intergeneration method can avoid the gap defects between the separation layer and the substrate, and form a strong COF composite membrane with strict interface compatibility, in order to solve the above problems. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a nanofiltration membrane containing a COFs interlayer for separating monovalent and divalent ions, thereby improving the trade-off effect of the nanofiltration membrane in the existing process.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a TpPa-COF sandwich nanofiltration membrane, the specific steps of which are as follows: (1) Preparation of TpPa-COF film Prepare 2 mol / L sodium hydroxide solution, soak the base membrane in the prepared sodium hydroxide solution, keep it in a constant temperature water bath at 60 ℃ for 2 h, take out the membrane and wash it with pure water for 3 times, and then soak it in pure water for 24 h for use; the substances involved in the preparation process of TpPa-COF film are composed of the following mass percentages: 0.5-2.5% diamine organic matter, a certain amount of 1,3,5-triformylphloroglucinol, 0.05-0.2% oxidant, and the rest are ultrapure water and organic solvent. Weigh a certain amount of oxidant powder, slowly add it to the diamine aqueous solution, then ultrasonically dissolve it for 0.1-1 h. After it is completely dissolved, solution 1 is obtained; prepare an organic solution of 1,3,5-triformylphloroglucinol of a certain concentration, and ultrasonically disperse it until it is completely dissolved to obtain solution 2; pour the two solutions into a beaker in a certain proportion, stir for 5-30 s, immerse the pretreated base film horizontally therein, and grow it in situ for 0.5-24 h, and then the TpPa-COF film can be introduced on the product.

[0007] (2) Preparation of aqueous and oil phase monomer solutions The substances involved in the preparation process of the aqueous monomer mixed solution are composed of the following mass percentages: 0.5-1.5% surfactant, 0.5-2.5% diamine compound, and the remainder is ultrapure water. Prepare a diamine aqueous solution of a certain concentration and stir it magnetically for 5-10 minutes. After all dissolved, add the surfactant dropwise. Stir the mixed solution magnetically for 10-15 minutes to obtain an aqueous monomer mixed solution; The substances involved in the preparation process of the oil phase monomer solution are composed according to the following mass percentages: 0.15-0.3% of 1,3,5-benzenetricarboxylic acid chloride and the remainder of n-hexane. 1,3,5-benzenetricarboxylic acid chloride is dissolved in n-hexane to prepare an oil phase solution, and ultrasonically dispersed for 5-10 minutes to obtain an oil phase solution.

[0008] (3) Preparation of nanofiltration membrane containing TpPa-COF sandwich The aqueous solution prepared in (2) is stirred evenly and then allowed to stand for 5 minutes for use. The membrane prepared in (1) is taken out from the pure water and excess water is wiped off with industrial wipe paper. 15-25 mL of the aqueous solution is poured on the surface of the base membrane and kept for 1-3 minutes. The excess aqueous solution is then wiped off with industrial wipe paper. Then 15-25 mL of the oil solution is poured in to allow interfacial polymerization to occur. After reacting for 1-2 minutes, the excess oil solution is poured out. After washing twice with n-hexane, the prepared nanofiltration membrane is placed in an oven and heated for 5-20 minutes. After drying, the membrane is taken out and immersed in ultrapure water for storage and use.

[0009] Preferably, the solvent of 1,3,5-triformylphloroglucinol in step (1) is one of ethanol, ether and methanol.

[0010] Preferably, the oxide in step (1) is one of dopamine hydrochloride, tannic acid and gallic acid.

[0011] Preferably, the commercial membrane in step (1) is one of polyacrylonitrile, polyvinylidene fluoride, polyether sulfone and polysulfone.

[0012] Preferably, the surfactant in step (2) is one of trimethylamine, triethylamine and dodecyldimethylbenzyl ammonium bromide.

[0013] Preferably, the diamine compound in step (2) is one of p-phenylenediamine, m-phenylenediamine and o-phenylenediamine.

[0014] The present invention proposes to prepare TpPa-COF thin film interlayers by interfacial polymerization and in-situ growth method respectively, and to prepare the surface polyamide layer by interfacial polymerization, so as to improve the hydrophilicity of the membrane and the removal capacity of divalent cations; it aims to break the trade-off effect of high separation effect and low flux in the treatment of mono / divalent cations by NF membrane, ensure the ideal water flux under the highest possible separation effect, and solve the difficulties of traditional NF membrane separation layer defects, easy pollution and low recycling. Two-dimensional COFs materials can effectively control the pore size distribution and hydrophobicity of the substrate surface, and improve the separation performance of the composite membrane. Beneficial Effects

[0015] TpPa-COF has the advantages of large specific surface area, high porosity, easy functionalization and strong design. Adding it as an interlayer into the NF membrane can adjust the hydrophilicity of the NF membrane and increase the membrane flux. The pores and charges of the material can enhance screening and electrostatic repulsion, which helps to break the trade-off effect between selectivity and flux to a certain extent.

[0016] Dopamine hydrochloride or phenol with catechol groups can be oxidized to quinones during the polymerization process. After oxidation, cyclization and rearrangement reactions, a metastable intermediate (5,6-dihydroxyindole) is formed, which can produce semiquinone free radicals and react with oxidized quinones. These free radicals are easily reoxidized and form ROS (O 2- ) and o-quinone. This one-step method allows the preparation of defect-free and dense COF films under mild ambient conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The surface scanning electron microscope image of the nanofiltration membrane of Example 1 is Figure 2 This is a surface scanning electron microscope image of the nanofiltration membrane of Example 5 Figure 3The surface scanning electron microscope image of the nanofiltration membrane of Example 7 is DETAILED DESCRIPTION

[0018] The present invention is further described in detail below by specific embodiments. However, those skilled in the art will appreciate that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention.

[0019] The zwitterionic nanofiltration membrane prepared by the present invention can be used to separate monovalent and divalent cations, so the retention rate of divalent cations, the permeability of monovalent cations and the water flux are three important parameters for evaluating the nanofiltration membrane.

[0020] The test conditions for water flux, retention rate of divalent cations, and permeability of monovalent cations are as follows: dead-end filtration device, inorganic salts selected from MgCl2 and LiCl, which are common in salt lake brine, with a total cation concentration of 1000 mg / L, Mg 2+ With Li + The mass ratio is 20:1, the test temperature is 25℃, pH=7, and the test pressure is 0.6 MPa.

[0021] The divalent cation (magnesium ion) retention rate is defined as:

[0022] Where R1 represents the magnesium ion retention rate, C p1 and C f1 are the magnesium ion concentrations in the permeate and feed solution, respectively.

[0023] The monovalent cation (lithium ion) rejection is defined as:

[0024] Where R2 represents the lithium ion retention rate, C p2 and C f2 are the lithium ion concentrations in the permeate and feed solution, respectively.

[0025] Water flux is defined as the volume of water that passes through the effective area of ​​the membrane per unit time under unit pressure. Example

[0026] (1) Prepare 2 mol / L sodium hydroxide solution, soak the commercial membrane in the prepared sodium hydroxide solution, keep it in a constant temperature water bath at 60℃ for 2 h, take out the membrane, wash it with pure water for 3 times, and then soak it in pure water for 24 h for use; weigh 2 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water at room temperature. After it is completely dissolved, weigh 0.2 g of dopamine hydrochloride and add it, and ultrasonically disperse it for 10 min to obtain solution 1; weigh 50 mg of 1,3,5-triformylphloroglucinol and add it to 50 mL of ethanol, and ultrasonically disperse it until the solution is clear to obtain solution 2; pour the two solutions into a beaker, stir for 10 s, put the pretreated base membrane into it, and grow it in situ for 12 h; then wash the membrane after the reaction with deionized water for 3 times, put it in a 120℃ oven to dry for 2 h, and put it in deionized water for use.

[0027] (2) Weigh 0.5 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water. Stir the mixture magnetically for 10 min. Add 0.5 mL of triethylamine and stir the mixture magnetically for 10 min to obtain an aqueous monomer mixed solution.

[0028] 1,3,5-Benzenetricarboxylic acid chloride was dissolved in n-hexane to prepare 50 mL of an oil phase solution with a concentration of 0.25% w / v, and ultrasonically dispersed until the solution was clear.

[0029] (3) Stir the aqueous solution prepared in (2) evenly and let it stand for 5 minutes for use. Take out the membrane prepared in (1) from the pure water and wipe off the excess water with industrial wipe paper. Pour 25 mL of the aqueous solution on the surface of the base membrane and keep it for 90 seconds. Then wipe off the excess aqueous solution with industrial wipe paper, and then pour in 25 mL of the oil solution to undergo interfacial polymerization reaction. After reacting for 2 minutes, pour out the excess oil solution. After rinsing twice with n-hexane, put the prepared nanofiltration membrane into an oven and heat it for 20 minutes. After drying, take it out and soak it in ultrapure water. The membrane is stored for use.

[0030] The performance of the nanofiltration membrane prepared in Example 1 was tested, and the water flux of the nanofiltration membrane was 49.8 L·m -2 ·h -1 bar -1 , Li + The retention rate is 38.3%, Mg 2+ The interception rate is 95.1%. Example

[0031] (1) Prepare 2 mol / L sodium hydroxide solution, soak the commercial membrane in the prepared sodium hydroxide solution, keep it in a constant temperature water bath at 60℃ for 2 h, take out the membrane, wash it with pure water for 3 times, and then soak it in pure water for 24 h for use; weigh 2 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water at room temperature. After it is completely dissolved, weigh 0.2 g of dopamine hydrochloride and add it, and ultrasonically disperse it for 10 min to obtain solution 1; weigh 50 mg of 1,3,5-triformylphloroglucinol and add it to 50 mL of methanol, and ultrasonically disperse it until the solution is clear to obtain solution 2; pour the two solutions into a beaker, stir for 10 s, put the pretreated base membrane into it, and grow it in situ for 12 h; then wash the membrane after the reaction with deionized water for 3 times, put it in a 120℃ oven to dry for 2 h, and put it in deionized water for use.

[0032] (2) Weigh 0.5 g of o-phenylenediamine and dissolve it in 50 mL of ultrapure water. Stir the mixture magnetically for 10 min. Add 0.5 mL of triethylamine and stir the mixture magnetically for 10 min to obtain an aqueous monomer mixed solution.

[0033] 1,3,5-Benzenetricarboxylic acid chloride was dissolved in n-hexane to prepare 50 mL of an oil phase solution with a concentration of 0.25% w / v, and ultrasonically dispersed until the solution was clear.

[0034] (3) Stir the aqueous solution prepared in (2) evenly and let it stand for 5 minutes for use. Take out the membrane prepared in (1) from the pure water and wipe off the excess water with industrial wipe paper. Pour 25 mL of the aqueous solution on the surface of the base membrane and keep it for 90 seconds. Then wipe off the excess aqueous solution with industrial wipe paper, and then pour in 25 mL of the oil solution to undergo interfacial polymerization reaction. After reacting for 2 minutes, pour out the excess oil solution. After rinsing twice with n-hexane, put the prepared nanofiltration membrane into an oven and heat it for 20 minutes. After drying, take it out and soak it in ultrapure water. The membrane is stored for use.

[0035] The performance of the nanofiltration membrane prepared in Example 2 was tested, and the water flux of the nanofiltration membrane was 39.8 L·m -2 ·h -1 bar -1 , Li + The retention rate is 40.3%, Mg 2+ The interception rate is 98.1%. Example

[0036] (1) Prepare 2 mol / L sodium hydroxide solution, soak the commercial membrane in the prepared sodium hydroxide solution, keep it in a constant temperature water bath at 60℃ for 2 h, take out the membrane, wash it with pure water for 3 times, and then soak it in pure water for 24 h for use; weigh 1.5 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water at room temperature. After it is completely dissolved, weigh 0.15 g of dopamine hydrochloride and add it, and ultrasonically disperse it for 10 min to obtain solution 1; weigh 50 mg of 1,3,5-triformylphloroglucinol and add it to 50 mL of ethanol, and ultrasonically disperse it until the solution is clear to obtain solution 2; pour the two solutions into a beaker, stir for 10 s, put the pretreated base membrane into it, and grow it in situ for 12 h; then wash the membrane after the reaction with deionized water for 3 times, put it in a 120℃ oven to dry for 2 h, and put it in deionized water for use.

[0037] (2) Weigh 1 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water. Stir the mixture magnetically for 10 min. Add 0.5 mL of triethylamine and stir the mixture magnetically for 10 min to obtain an aqueous monomer mixed solution.

[0038] 1,3,5-Benzenetricarboxylic acid chloride was dissolved in n-hexane to prepare 50 mL of an oil phase solution with a concentration of 0.25% w / v, and ultrasonically dispersed until the solution was clear.

[0039] (3) Stir the aqueous solution prepared in (2) evenly and let it stand for 5 minutes for use. Take out the membrane prepared in (1) from the pure water and wipe off the excess water with industrial wipe paper. Pour 25 mL of the aqueous solution on the surface of the base membrane and keep it for 90 seconds. Then wipe off the excess aqueous solution with industrial wipe paper, and then pour in 25 mL of the oil solution to undergo interfacial polymerization reaction. After reacting for 2 minutes, pour out the excess oil solution. After rinsing twice with n-hexane, put the prepared nanofiltration membrane into an oven and heat it for 20 minutes. After drying, take it out and soak it in ultrapure water. The membrane is stored for use.

[0040] The performance of the nanofiltration membrane prepared in Example 3 was tested, and the water flux of the nanofiltration membrane was 42.4 L·m -2 ·h -1 bar -1 , Li + The retention rate is 33.3%, Mg 2+ The interception rate is 96.1%. Example

[0041] (1) Prepare 2 mol / L sodium hydroxide solution, soak the commercial membrane in the prepared sodium hydroxide solution, keep it in a constant temperature water bath at 60℃ for 2 h, take out the membrane, wash it with pure water for 3 times, and then soak it in pure water for 24 h for use; weigh 1.5 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water at room temperature. After it is completely dissolved, weigh 0.15 g of gallic acid and add it, and ultrasonically disperse it for 10 min to obtain solution 1; weigh 50 mg of 1,3,5-triformylphloroglucinol and add it to 50 mL of ethanol, and ultrasonically disperse it until the solution is clear to obtain solution 2; pour the two solutions into a beaker, stir for 10 s, put the pretreated base membrane into it, and grow it in situ for 12 h; then wash the membrane after the reaction with deionized water for 3 times, put it in a 120℃ oven to dry for 2 h, and put it in deionized water for use.

[0042] (2) Weigh 1 g of m-phenylenediamine and dissolve it in 50 mL of ultrapure water. Stir the mixture magnetically for 10 min. Add 0.5 mL of triethylamine and stir the mixture magnetically for 10 min to obtain an aqueous monomer mixed solution.

[0043] 1,3,5-Benzenetricarboxylic acid chloride was dissolved in n-hexane to prepare 50 mL of an oil phase solution with a concentration of 0.25% w / v, and ultrasonically dispersed until the solution was clear.

[0044] (3) Stir the aqueous solution prepared in (2) evenly and let it stand for 5 minutes for use. Take out the membrane prepared in (1) from the pure water and wipe off the excess water with industrial wipe paper. Pour 25 mL of the aqueous solution on the surface of the base membrane and keep it for 90 seconds. Then wipe off the excess aqueous solution with industrial wipe paper, and then pour in 25 mL of the oil solution to undergo interfacial polymerization reaction. After reacting for 2 minutes, pour out the excess oil solution. After rinsing twice with n-hexane, put the prepared nanofiltration membrane into an oven and heat it for 20 minutes. After drying, take it out and soak it in ultrapure water. The membrane is stored for use.

[0045] The performance of the nanofiltration membrane prepared in Example 4 was tested, and the water flux of the nanofiltration membrane was 40.4 L·m -2 ·h -1 bar -1 , Li + The retention rate was 29.3%, Mg 2+ The interception rate is 96.2%. Example

[0046] (1) Prepare 2 mol / L sodium hydroxide solution, soak the commercial membrane in the prepared sodium hydroxide solution, keep it in a constant temperature water bath at 60℃ for 2 h, take out the membrane, wash it with pure water for 3 times, and then soak it in pure water for 24 h for use; weigh 2 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water at room temperature. After it is completely dissolved, weigh 0.2 g of dopamine hydrochloride and add it, and ultrasonically disperse it for 10 min to obtain solution 1; weigh 50 mg of 1,3,5-triformylphloroglucinol and add it to 50 mL of ethanol, and ultrasonically disperse it until the solution is clear to obtain solution 2; pour the two solutions into a beaker, stir for 10 s, put the pretreated base membrane into it, and grow it in situ for 24 h; then wash the membrane after the reaction with deionized water for 3 times, put it in a 120℃ oven to dry for 2 h, and put it in deionized water for use.

[0047] (2) Weigh 0.5 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water. Stir the mixture magnetically for 10 min. Add 0.5 mL of triethylamine and stir the mixture magnetically for 10 min to obtain an aqueous monomer mixed solution.

[0048] Dissolve 1,3,5-benzenetricarboxylic acid chloride in n-hexane to prepare 50 mL of oil phase solution with a concentration of 0.25% w / v, and disperse by ultrasonic until the solution is clear. (3) Stir the aqueous solution prepared in (2) evenly and let it stand for 5 minutes for use. Take out the membrane prepared in (1) from the pure water and wipe off the excess water with industrial wipe paper. Pour 25 mL of the aqueous solution on the surface of the base membrane and keep it for 90 seconds. Then wipe off the excess aqueous solution with industrial wipe paper, and then pour in 25 mL of the oil solution to undergo interfacial polymerization reaction. After reacting for 2 minutes, pour out the excess oil solution. After rinsing twice with n-hexane, put the prepared nanofiltration membrane into an oven and heat it for 20 minutes. After drying, take it out and soak it in ultrapure water. The membrane is stored for use.

[0049] The performance of the nanofiltration membrane prepared in Example 5 was tested, and the water flux of the nanofiltration membrane was 40.8 L·m -2 ·h -1 bar -1 , Li + The retention rate is 29.5%, Mg 2+ The interception rate is 98.5%. Example

[0050] (1) Prepare 2 mol / L sodium hydroxide solution, soak the commercial membrane in the prepared sodium hydroxide solution, keep it in a constant temperature water bath at 60℃ for 2 h, take out the membrane, wash it with pure water for 3 times, and then soak it in pure water for 24 h for use; weigh 2 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water at room temperature. After it is completely dissolved, weigh 0.2 g of tannic acid and add it, and ultrasonically disperse it for 10 min to obtain solution 1; weigh 50 mg of 1,3,5-triformylphloroglucinol and add it to 50 mL of ether, and ultrasonically disperse it until the solution is clear to obtain solution 2; pour the two solutions into a beaker, stir for 10 s, put the pretreated base membrane into it, and grow it in situ for 24 h; then wash the membrane after the reaction with deionized water for 3 times, put it in a 120℃ oven to dry for 2 h, and put it in deionized water for use.

[0051] (2) Weigh 0.5 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water. Stir the mixture magnetically for 10 min. Add 0.5 mL of trimethylamine and stir the mixture magnetically for 10 min to obtain an aqueous monomer mixed solution.

[0052] 1,3,5-Benzenetricarboxylic acid chloride was dissolved in n-hexane to prepare 50 mL of an oil phase solution with a concentration of 0.25% w / v, and ultrasonically dispersed until the solution was clear.

[0053] (3) Stir the aqueous solution prepared in (2) evenly and let it stand for 5 minutes for later use. Take out the membrane prepared in (1) from the pure water and wipe off the excess water with industrial wipe paper. Pour 25 mL of the aqueous solution on the surface of the base membrane and keep it for 90 seconds. Then wipe off the excess aqueous solution with industrial wipe paper, and then pour in 25 mL of the oil solution to undergo interfacial polymerization reaction. After reacting for 2 minutes, pour out the excess oil solution. After rinsing twice with n-hexane, put the prepared nanofiltration membrane into an oven and heat it for 20 minutes. After drying, take it out and soak it in ultrapure water. The membrane is stored for use.

[0054] The performance of the nanofiltration membrane prepared in Example 6 was tested, and the water flux of the nanofiltration membrane was 49.8 L·m -2 ·h -1 bar -1 , Li + The retention rate is 38.5%, Mg 2+ The interception rate is 97.5%. Example

[0055] (1) Prepare 2 mol / L sodium hydroxide solution, soak the commercial membrane in the prepared sodium hydroxide solution, keep it in a constant temperature water bath at 60℃ for 2 h, take out the membrane, wash it with pure water for 3 times, and then soak it in pure water for 24 h for use; weigh 1.5 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water at room temperature. After it is completely dissolved, weigh 0.15 g of dopamine hydrochloride and add it, and ultrasonically disperse it for 10 min to obtain solution 1; weigh 50 mg of 1,3,5-triformylphloroglucinol and add it to 50 mL of ethanol, and ultrasonically disperse it until the solution is clear to obtain solution 2; pour the two solutions into a beaker, stir for 10 s, put the pretreated base membrane into it, and grow it in situ for 24 h; then wash the membrane after the reaction with deionized water for 3 times, put it in a 120℃ oven to dry for 2 h, and put it in deionized water for use.

[0056] (2) Weigh 1 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water. Stir the mixture magnetically for 10 min. Add 0.5 mL of triethylamine and stir the mixture magnetically for 10 min to obtain an aqueous monomer mixed solution.

[0057] 1,3,5-Benzenetricarboxylic acid chloride was dissolved in n-hexane to prepare 50 mL of an oil phase solution with a concentration of 0.25% w / v, and ultrasonically dispersed until the solution was clear.

[0058] (3) Stir the aqueous solution prepared in (2) evenly and let it stand for 5 minutes for use. Take out the membrane prepared in (1) from the pure water and wipe off the excess water with industrial wipe paper. Pour 25 mL of the aqueous solution on the surface of the base membrane and keep it for 90 seconds. Then wipe off the excess aqueous solution with industrial wipe paper, and then pour in 25 mL of the oil solution to undergo interfacial polymerization reaction. After reacting for 2 minutes, pour out the excess oil solution. After rinsing twice with n-hexane, put the prepared nanofiltration membrane into an oven and heat it for 20 minutes. After drying, take it out and soak it in ultrapure water. The membrane is stored for use.

[0059] The performance of the nanofiltration membrane prepared in Example 7 was tested, and the water flux of the nanofiltration membrane was 50.8 L·m -2 ·h -1 bar -1 , Li + The retention rate is 32.6%, Mg 2+ The interception rate is 96.7%. Example

[0060] (1) Prepare 2 mol / L sodium hydroxide solution, soak the commercial membrane in the prepared sodium hydroxide solution, keep it in a constant temperature water bath at 60℃ for 2 h, take out the membrane, wash it with pure water for 3 times, and then soak it in pure water for 24 h for use; weigh 2 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water at room temperature. After it is completely dissolved, weigh 0.2 g of dopamine hydrochloride and add it, and ultrasonically disperse it for 10 min to obtain solution 1; weigh 50 mg of 1,3,5-triformylphloroglucinol and add it to 50 mL of ethanol, and ultrasonically disperse it until the solution is clear to obtain solution 2; pour the two solutions into a beaker, stir for 10 s, put the pretreated base membrane into it, and grow it in situ for 2 h; then wash the membrane after the reaction with deionized water for 3 times, put it in a 120℃ oven to dry for 2 h, and put it in deionized water for use.

[0061] (2) Weigh 0.5 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water. Stir the mixture magnetically for 10 min. Add 0.5 mL of triethylamine and stir the mixture magnetically for 10 min to obtain an aqueous monomer mixed solution.

[0062] 1,3,5-Benzenetricarboxylic acid chloride was dissolved in n-hexane to prepare 50 mL of an oil phase solution with a concentration of 0.25% w / v, and ultrasonically dispersed until the solution was clear.

[0063] (3) Stir the aqueous solution prepared in (2) evenly and let it stand for 5 minutes for use. Take out the membrane prepared in (1) from the pure water and wipe off the excess water with industrial wipe paper. Pour 25 mL of the aqueous solution on the surface of the base membrane and keep it for 90 seconds. Then wipe off the excess aqueous solution with industrial wipe paper, and then pour in 25 mL of the oil solution to undergo interfacial polymerization reaction. After reacting for 2 minutes, pour out the excess oil solution. After rinsing twice with n-hexane, put the prepared nanofiltration membrane into an oven and heat it for 20 minutes. After drying, take it out and soak it in ultrapure water. The membrane is stored for use.

[0064] The performance of the nanofiltration membrane prepared in Example 8 was tested, and the water flux of the nanofiltration membrane was 56.8 L·m -2 ·h -1 bar -1 , Li + The retention rate is 36.6%, Mg 2+ The interception rate is 96.3%. Example

[0065] (1) Prepare 2 mol / L sodium hydroxide solution, soak the commercial membrane in the prepared sodium hydroxide solution, keep it in a constant temperature water bath at 60℃ for 2 h, take out the membrane, wash it with pure water for 3 times, and then soak it in pure water for 24 h for use; weigh 2 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water at room temperature. After it is completely dissolved, weigh 0.2 g of dopamine hydrochloride and add it, and ultrasonically disperse it for 10 min to obtain solution 1; weigh 50 mg of 1,3,5-triformylphloroglucinol and add it to 50 mL of methanol, and ultrasonically disperse it until the solution is clear to obtain solution 2; pour the two solutions into a beaker, stir for 10 s, put the pretreated base membrane into it, and grow it in situ for 2 h; then wash the membrane after the reaction with deionized water for 3 times, put it in a 120℃ oven to dry for 2 h, and put it in deionized water for use.

[0066] (2) Weigh 0.5 g of m-phenylenediamine and dissolve it in 50 mL of ultrapure water. Stir the mixture magnetically for 10 min. Add 0.5 mL of triethylamine and stir the mixture magnetically for 10 min to obtain an aqueous monomer mixed solution.

[0067] 1,3,5-Benzenetricarboxylic acid chloride was dissolved in n-hexane to prepare 50 mL of an oil phase solution with a concentration of 0.25% w / v, and ultrasonically dispersed until the solution was clear.

[0068] (3) Stir the aqueous solution prepared in (2) evenly and let it stand for 5 minutes for use. Take out the membrane prepared in (1) from the pure water and wipe off the excess water with industrial wipe paper. Pour 25 mL of the aqueous solution on the surface of the base membrane and keep it for 90 seconds. Then wipe off the excess aqueous solution with industrial wipe paper, and then pour in 25 mL of the oil solution to undergo interfacial polymerization reaction. After reacting for 2 minutes, pour out the excess oil solution. After rinsing twice with n-hexane, put the prepared nanofiltration membrane into an oven and heat it for 20 minutes. After drying, take it out and soak it in ultrapure water. The membrane is stored for use.

[0069] The performance of the nanofiltration membrane prepared in Example 9 was tested, and the water flux of the nanofiltration membrane was 42.8 L·m -2 ·h -1 bar -1 , Li + The retention rate is 34.5%, Mg 2+ The interception rate is 97.3%.

[0070] Embodiment 10: (1) Prepare 2 mol / L sodium hydroxide solution, soak the commercial membrane in the prepared sodium hydroxide solution, keep it in a constant temperature water bath at 60℃ for 2 h, take out the membrane, wash it with pure water for 3 times, and then soak it in pure water for 24 h for use; weigh 1.5 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water at room temperature. After it is completely dissolved, weigh 0.15 g of dopamine hydrochloride and add it, and ultrasonically disperse it for 10 min to obtain solution 1; weigh 50 mg of 1,3,5-triformylphloroglucinol and add it to 50 mL of ethanol, and ultrasonically disperse it until the solution is clear to obtain solution 2; pour the two solutions into a beaker, stir for 10 s, put the pretreated base membrane into it, and grow it in situ for 2 h; then wash the membrane after the reaction with deionized water for 3 times, put it in a 120℃ oven to dry for 2 h, and put it in deionized water for use.

[0071] (2) Weigh 1 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water. Stir the mixture magnetically for 10 min. Add 0.5 mL of triethylamine and stir the mixture magnetically for 10 min to obtain an aqueous monomer mixed solution.

[0072] 1,3,5-Benzenetricarboxylic acid chloride was dissolved in n-hexane to prepare 50 mL of an oil phase solution with a concentration of 0.25% w / v, and ultrasonically dispersed until the solution was clear.

[0073] (3) Stir the aqueous solution prepared in (2) evenly and let it stand for 5 minutes for use. Take out the membrane prepared in (1) from the pure water and wipe off the excess water with industrial wipe paper. Pour 25 mL of the aqueous solution on the surface of the base membrane and keep it for 90 seconds. Then wipe off the excess aqueous solution with industrial wipe paper, and then pour in 25 mL of the oil solution to undergo interfacial polymerization reaction. After reacting for 2 minutes, pour out the excess oil solution. After rinsing twice with n-hexane, put the prepared nanofiltration membrane into an oven and heat it for 20 minutes. After drying, take it out and soak it in ultrapure water. The membrane is stored for use.

[0074] The performance test of the nanofiltration membrane prepared in Example 10 showed that the water flux of the nanofiltration membrane was 48.8 L·m -2 ·h -1 bar -1 , Li + The retention rate is 30.6%, Mg 2+ The interception rate is 98.3%.

[0075] Embodiment 11: (1) Prepare 2 mol / L sodium hydroxide solution, soak the commercial membrane in the prepared sodium hydroxide solution, and keep it in a constant temperature water bath at 60℃ for 2 h. Take out the membrane and wash it with pure water for 3 times, and then soak it in pure water for 24 h for use. Under room temperature, weigh 0.5 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water. After it is completely dissolved, weigh 0.05 g of dopamine hydrochloride and add it. Ultrasonic dispersion is performed for 10 min to obtain solution 1. Weigh 50 mg of 1,3,5-triformylphloroglucinol and add it to 50 mL of ethanol. Ultrasonic dispersion is performed until the solution is clear to obtain solution 2. Pour the two solutions into a beaker, stir for 10 s, put the pretreated base membrane into it, and grow it in situ for 12 h. Then, wash the membrane after the reaction with deionized water for 3 times, put it in a 120℃ oven to dry for 2 h, and put it in deionized water for use.

[0076] (2) Weigh 1 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water. Stir the mixture magnetically for 10 min. Add 0.5 mL of triethylamine and stir the mixture magnetically for 10 min to obtain an aqueous monomer mixed solution.

[0077] 1,3,5-Benzenetricarboxylic acid chloride was dissolved in n-hexane to prepare 50 mL of an oil phase solution with a concentration of 0.25% w / v, and ultrasonically dispersed until the solution was clear.

[0078] (3) Stir the aqueous solution prepared in (2) evenly and let it stand for 5 minutes for use. Take out the membrane prepared in (1) from the pure water and wipe off the excess water with industrial wipe paper. Pour 25 mL of the aqueous solution on the surface of the base membrane and keep it for 90 seconds. Then wipe off the excess aqueous solution with industrial wipe paper, and then pour in 25 mL of the oil solution to undergo interfacial polymerization reaction. After reacting for 2 minutes, pour out the excess oil solution. After rinsing twice with n-hexane, put the prepared nanofiltration membrane into an oven and heat it for 20 minutes. After drying, take it out and soak it in ultrapure water. The membrane is stored for use.

[0079] The performance of the nanofiltration membrane prepared in Example 11 was tested, and the water flux of the nanofiltration membrane was 45.8 L·m -2 ·h -1 bar -1 , Li + The retention rate is 33.2%, Mg 2+ The interception rate is 98.7%.

[0080] Embodiment 12: (1) Prepare 2 mol / L sodium hydroxide solution, soak the commercial membrane in the prepared sodium hydroxide solution, keep it in a constant temperature water bath at 60°C for 2 h, take out the membrane, wash it with pure water three times, and then soak it in pure water for 24 h for use; weigh 0.5 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water at room temperature. After it is completely dissolved, weigh 0.05 g of dopamine hydrochloride and add it thereto, and ultrasonically disperse it for 10 min to obtain solution 1; weigh 50 mg of 1,3,5-triformylphloroglucinol and add it to 50 mL of ethanol, and ultrasonically disperse it until the solution is clear to obtain solution 1; pour the two solutions into a beaker, stir for 10 s, put the pretreated base membrane into it, and grow it in situ for 12 h; then wash the membrane after the reaction with deionized water three times, put it in a 120°C oven to dry for 2 h after washing, and put it in deionized water for use after drying.

[0081] (2) Weigh 0.7 g of p-phenylenediamine and dissolve it in 50 mL of ultrapure water. Stir the mixture magnetically for 10 min. Add 0.5 mL of triethylamine and stir the mixture magnetically for 10 min to obtain an aqueous monomer mixed solution.

[0082] 1,3,5-Benzenetricarboxylic acid chloride was dissolved in n-hexane to prepare 50 mL of an oil phase solution with a concentration of 0.25% w / v, and ultrasonically dispersed until the solution was clear.

[0083] (3) Stir the aqueous solution prepared in (2) evenly and let it stand for 5 minutes for use. Take out the membrane prepared in (1) from the pure water and wipe off the excess water with industrial wipe paper. Pour 25 mL of the aqueous solution on the surface of the base membrane and keep it for 90 seconds. Then wipe off the excess aqueous solution with industrial wipe paper, and then pour in 25 mL of the oil solution to undergo interfacial polymerization reaction. After reacting for 2 minutes, pour out the excess oil solution. After rinsing twice with n-hexane, put the prepared nanofiltration membrane into an oven and heat it for 20 minutes. After drying, take it out and soak it in ultrapure water. The membrane is stored for use.

[0084] The performance of the nanofiltration membrane prepared in Example 12 was tested, and the water flux of the nanofiltration membrane was 40.8 L·m -2 ·h -1 bar -1 , Li + The retention rate is 35.2%, Mg 2+ The interception rate is 97.7%.

Claims

1. A method for preparing a TpPa-COF sandwich nanofiltration membrane, the specific steps of which are as follows: (1) Preparation of TpPa-COF film Prepare 2 mol / L sodium hydroxide solution, soak the base film in the prepared sodium hydroxide solution, keep it in a constant temperature water bath at 60 ℃ for 2 h, take out the membrane and wash it with pure water 3 times, then soak it in pure water for 24 h for use; the substances involved in the preparation process of TpPa-COF film are composed of the following mass percentages: 0.5-2.5% diamine organic matter, a certain amount of 1,3,5-triformyl phloroglucinol, 0.05-0.2% oxidant, and the remaining amount is ultrapure water and organic solvent. Weigh a certain amount of oxidant powder, slowly add it to the diamine aqueous solution, and then ultrasonically dissolve it for 0.1-1 h. After it is completely dissolved, solution 1 is obtained; prepare a certain concentration of 1,3,5-triformyl phloroglucinol organic solution, ultrasonically disperse it until it is completely dissolved, and obtain solution 2; pour the two solutions into a beaker in a certain proportion, stir for 5-30 s, and immerse the pretreated base film horizontally therein, The TpPa-COF film can be introduced on the product after in-situ growth for 0.5-24h; (2) Preparation of aqueous and oil phase monomer solutions The substances involved in the preparation process of the aqueous monomer mixed solution are composed of the following mass percentages: 0.5-1.5% surfactant, 0.5-2.5% diamine compound, and the remainder is ultrapure water. Prepare a diamine aqueous solution of a certain concentration and stir it magnetically for 5-10 minutes. After all dissolved, add the surfactant dropwise. Stir the mixed solution magnetically for 10-15 minutes to obtain an aqueous monomer mixed solution; The substances involved in the preparation process of the oil phase monomer solution are composed according to the following mass percentages: 0.15-0.3% of 1,3,5-benzenetricarboxylic acid chloride and the remainder of n-hexane. 1,3,5-benzenetricarboxylic acid chloride is dissolved in n-hexane to prepare an oil phase solution, and ultrasonically dispersed for 5-10 minutes to obtain an oil phase solution; (3) Preparation of nanofiltration membrane containing TpPa-COF sandwich The aqueous solution prepared in (2) is stirred evenly and then allowed to stand for 5 minutes for use. The membrane prepared in (1) is taken out from the pure water and excess water is wiped off with industrial wipe paper. 15-25 mL of the aqueous solution is poured on the surface of the base membrane and kept for 1-3 minutes. The excess aqueous solution is then wiped off with industrial wipe paper. Then 15-25 mL of the oil solution is poured in to allow interfacial polymerization to occur. After reacting for 1-2 minutes, the excess oil solution is poured out. After washing twice with n-hexane, the prepared nanofiltration membrane is placed in an oven and heated for 5-20 minutes. After drying, the membrane is taken out and immersed in ultrapure water for storage and use.

2. The preparation method according to claim 1, characterized in that In step (1), the solvent of 1,3,5-triformylphloroglucinol is one of ethanol, ether and methanol.

3. The preparation method according to claim 1, characterized in that In step (1), the oxide is one of dopamine hydrochloride, tannic acid and gallic acid.

4. The preparation method according to claim 1, characterized in that In step (1), the base film is one of polyacrylonitrile, polyvinylidene fluoride, polyether sulfone and polysulfone.

5. The preparation method according to claim 1, characterized in that The surfactant in step (2) is one of trimethylamine, triethylamine and dodecyldimethylbenzyl ammonium bromide.

6. The preparation method according to claim 1, characterized in that The diamine compound in step (2) is one of p-phenylenediamine, m-phenylenediamine and o-phenylenediamine.

7. A method for preparing a COFs sandwich nanofiltration membrane according to any one of claims 1 to 5, wherein the prepared TpPa-COF sandwich nanofiltration membrane is characterized in that: The pure water flux of the nanofiltration membrane is ≥40 L·m -2 ·h -1 bar -1 In the separation test of monovalent and divalent cations, the retention rate of monovalent ions such as lithium ions is ≤40%, the retention rate of divalent ions such as magnesium ions is ≥95%, and the membrane flux recovery rate is ≥95%, which has obvious anti-biological pollution effect.

Citation Information

Patent Citations

  • Preparation method of post-modified COF (at) Dopamine composite membrane and application of post-modified COF (at) Dopamine composite membrane in ion separation

    CN118615874A

  • Method for preparing loose nanofiltration membrane based on interfacial polymerization

    CN110180402A

  • Preparation method of polytetrafluoroethylene composite nanofiltration membrane with sandwich structure

    CN111467977A

  • Nanofiltration membrane and preparation method thereof

    CN118807467A

  • Synthesis of covalent organic membranes and use thereof

    IN201611009671A

Cited By

  • Positively-charged composite membrane based on sulfonated COF interlayer and application of positively-charged composite membrane

    CN120662149A

  • Preparation of COF-polyamide hybrid nanofiltration membrane and application of COF-polyamide hybrid nanofiltration membrane in wastewater treatment

    CN121103161A

  • Preparation method of strong interlayer bonding nanofiltration membrane constructed by solid-liquid interfacial polymerization and product and application thereof

    CN121775689A